Diversity of marine tunicate from waters of Pannikiang Island and Badi Island of South Sulawesi, Indonesia - Magdalena Litaay; Rensi Piri; Naspira Binti Jabir; Dody Priosambodo; Ayub Wirabuana Putra (Society for Indonesian Biodiversity, 2023)
Abstract. Litaay M, Piri R, Jabir NB, Priosambodo D, Putra AW. 2023. Diversity of marine tunicate from waters of Pannikiang Island and Badi Island of South Sulawesi, Indonesia. Biodiversitas 24: 1431-1437. The number of tunicates is currently known for approximately 3000 species, but it is estimated that there are still 1000-2000 more species that have not been described globally. The Spermonde Archipelago in South Sulawesi is a habitat for various tunicates, but not all islands have been well explored. This study aims to expand the distribution map of tunicates in Spermonde Archipelago, especially in the two study islands (Pannikiang Island and Badi Island). The diversity of tunicates between two islands, which have different ecological conditions, is compared in this study. This study used a line transect method along 20 m with a combination of plots at a depth of 5 meters. A transect was applied at four different locations according to wind direction. All tunicates inside the transect were recorded, counted, and sub-sample were collected for identification purposes. The data obtained were analyzed using the diversity index (Chao-1, Shannon-wiener, Uniformity, and Dominance). There are a total of 35 species (24 species at Pannikiang Island and 18 at Badi Island). Nephtheis fascicularis, Didemnum molle, Clavelina robusta, and Polycarpa aurata can be found on both islands. The levels of diversity of the two islands differ with little in common.